Thermally Durable Nonfullerene Acceptor with Nonplanar Conjugated Backbone for High‐Performance Organic Solar Cells. Issue 12 (17th February 2020) - Cho, Hye Won; An, Na Gyeong; Park, Song Yi; Shin, Yun Seop; Lee, Woojin; Kim, Jin Young; Song, Suhee
Abstract: A nonfullerene acceptor (NFA) with acceptor–donor–acceptor (A–D–A) architecture, i‐IEICO‐2F, based on 4, 9‐dihydro‐ s ‐indaceno[1, 2‐ b :5, 6‐ b ′]dithiophene as an electron‐donating core and 2‐(6‐fluoro‐2, 3‐dihydro‐3‐oxo‐1 H ‐inden‐1‐ylidene)‐propanedinitrile as electron‐withdrawing end groups, is designed and synthesized. i‐IEICO‐2F has a twist structure in the main conjugated chain, which causes blueshifted absorption and leads to harmonious absorption with a high bandgap donor. The bandgap of i‐IEICO‐2F compliments the bandgap of suitable wide bandgap donor polymers such as J52, leading to complete light absorption throughout the visible spectrum. Devices based on i‐IEICO‐2F exhibit optimized photovoltaic performance including an open‐circuit voltage of 0.93 V, a short‐circuit current density of 16.61 mA cm −2, and a fill factor of 73%, and result in a power conversion efficiency (PCE) of 11.28%. The i‐IEICO‐2F‐based devices reach PCEs of >11% without using any additives or post‐treatments. Devices are found to be thermally stable and maintain 44% of their initial PCE after 184.5 h of continuous thermal annealing (TA) treatment at 150 °C. Based on UV, atomic force microscopy (AFM), and grazing incidence wide angle X‐ray scattering (GIWAXS) results, i‐IEICO‐2F devices show almost identical morphology and molecular orientation throughout the TA treatment and excellent stability compared to other IEICO derivatives. Abstract : A new nonfullerene acceptor (NFA) with acceptor–donor–acceptor (A–D–A) architecture, i‐IEICO‐2F, is designed and synthesized. Devices based on i‐IEICO‐2F exhibit optimized photovoltaic performance with a power conversion efficiency (PCE) of 11.28%. Devices are found to be thermally stable and maintain 44% of their initial PCE after 184.5 h of continuous thermal annealing treatment at 150 °C.